Liquid-liquid-phase synthesis of exo-vinylene carbonates from primary propargylic alcohols: catalyst design and recycling - Johnson, Chloe; Dabral, Saumya; Rudolf, Peter; Licht, Ulrike; Hashmi, A. Stephen K.; Schaub, Thomas (ChemCatChem, 2021)
A straight-forward approach to separate catalyst from the exo-vinylene carbonate (EVC) products of the carboxylative cyclisation of primary propargylic alcohols has been developed. The liquid-liquid phase synthesis utilises lipophilic silver(I) carboxylate salts and N,N-dioctyl modified phosphine (FatPhos) ligands to enhance catalyst solubility in non-polar solvents. Following simple liquid-liquid phase separation, EVCs relevant as monomers for poly(urethane) and poly(carbonate) synthesis were isolated in the non-miscible polar phase in good yields. In situ reaction monitoring by ReactIR gave insights into the reaction kinetics and informed the conditions used to afford good EVC selectivity. Under optimised conditions, silver leaching into the product phase was very minor as confirmed by ICP-MS. Furthermore, a protocol for catalyst recycling by liquid-liquid separation was demonstrated, with modest loss of catalytic activity over 3 runs.